Penerapan Perilaku Hidup Bersih dan Sehat (PHBS) Pada Siswa Sekolah SMP Muhammadiyah 61 Tanjung Slamet - Dea Ananda Br.SK; Keyla Harista Nasution; Muthia Afrah Goslan Siregar; Nur Asiyah Siregar; Nurfaizah Hasibuan; Raisa Shabrina Batu Bara; Sandiyatun Daulay; Nisrina Nisrina (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
PHBS (clean and healthy living behavior) is a movement that aims to improve the quality of life and public health. PHBS can be applied in households, schools, workplaces, and the general public. This research is a research analysis of clean and healthy living behavior (PHBS) of students in the Muhammadiyah 61 Tanjung Slamet Junior High School environment. This study aims to find out how the application of PHBS students of SMP Muhammadiyah 61 Tanjung Slamet in the school environment. The speakers conducted counseling in the form of lectures to self-students to be able to implement clean and healthy living behaviors at school, home and public places. This research was conducted with qualitative methods such as lecture and question and answer approaches. The qualitative method was chosen with the main aim of gaining a deep understanding of the views, understanding, and experiences possessed by participants related to the issue of applying clean and clean living behavior. This research was conducted through several stages, namely: lectures and questions and answers. Based on the results of research at SMP Muhammadiyah 61 Tanjung Slamet, there is still the behavior of students who have not implemented PHBS correctly. For example, rarely washing hands with soap and running water and also still found students and students who do not throw garbage in their place.